Trabalho dos professores: considerações sobre linguagem e experiência - Silva, Jolair da Costa (2012)
In times of rapid economic, scientific and technological transformation, it is necessary rethink the concepts and practices experienced. In this social context, it is notice that the work goes through changes in its configuration. Based on this presupposition, this dissertation investigated which relations the teachers establish in their speeches among language, experience and work. Therefore were interviewed ten teachers of Basic Education. The speeches were collected through semi-structures interviews according with hermeneutic principles and the data produced were analyzed based on hermeneutic analysis. This is because the hermeneutic searches possibilities for subjects to experience the expansion of living conditions are not disfigured or not failed. In the analysis of the interviews noticed the peculiarity of teacher‟s work in view of transformation praxis elements and instrumentation elements-tchne. It was possible observe as the first enriches the meaning of teacher‟s work. It allows the production of knowledge that generates transformation while the second element cooperates with the mischaracterization of meaning of teacher‟s work because it approaches of a work mentality. Thus, it is possible to notice that the teachers understand the language as formative and their experiences transpire in their self-understanding of a work as a mentor and trainer. .